2010
DOI: 10.1111/j.1742-4658.2010.07764.x
|View full text |Cite
|
Sign up to set email alerts
|

Tumor suppressor p16INK4a: Downregulation of galectin‐3, an endogenous competitor of the pro‐anoikis effector galectin‐1, in a pancreatic carcinoma model

Abstract: The tumor suppressor p16INK4a has functions beyond cell‐cycle control via cyclin‐dependent kinases. A coordinated remodeling of N‐ and O‐glycosylation, and an increase in the presentation of the endogenous lectin galectin‐1 sensing these changes on the surface of p16INK4a‐expressing pancreatic carcinoma cells (Capan‐1), lead to potent pro‐anoikis signals. We show that the p16INK4a‐dependent impact on growth‐regulatory lectins is not limited to galectin‐1, but also concerns galectin‐3. By monitoring its express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
83
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 120 publications
(85 citation statements)
references
References 50 publications
1
83
0
1
Order By: Relevance
“…However, it has been reported that Gal-1 and Gal-3 may have differential effects on ligand binding. 38,39 The possibility exists, therefore, that more pronounced effects on thrombus formation could be observed in single-knockout mice. …”
Section: Discussionmentioning
confidence: 99%
“…However, it has been reported that Gal-1 and Gal-3 may have differential effects on ligand binding. 38,39 The possibility exists, therefore, that more pronounced effects on thrombus formation could be observed in single-knockout mice. …”
Section: Discussionmentioning
confidence: 99%
“…On the biochemical side, counterreceptor characterization, for the protein/ lipid and its glycosylation, will define the first steps of the trigger cascade, from initial binding to signaling. In fact, Galectin-1 is known to target only few glycoconjugates despite the abundance of b-galactosides on the cell surface, the a 5 b 1 -integrin being especially relevant for growth regulation (56), and p16 INK4a -dependent reprogramming of counterreceptor expression and glycosylation may serve as precedent (27,28,57). That the counterreceptor(s), on the level of the protein and/or its glycosylation, may be subject to NF-kB-dependent regulation, as is the case for CD7 (a glycoprotein counterreceptor in apoptosis induction of activated T cells) in murine L7 lymphoma cells (58), is a tempting assumption.…”
Section: Discussionmentioning
confidence: 99%
“…La découverte d'agents thérapeutiques actifs contre les galectines n'en est qu'à ses prémices. Pour être efficaces tout en limitant les effets secondaires, les drogues antigalectines devront être sélectives d'une ou de plusieurs galectines qui peuvent avoir des effets antagonistes, par exemple pro-ou anti-anoïkis 1 [33], voire être spécifiques de la forme extra ou intracellulaire d'une galectine. Leur action devra être locale plutôt que systémique, et les voies d'administration ou de ciblage appropriées.…”
Section: Galectines : Des Cibles Thérapeutiques Potentielles ?unclassified